Serological field investigations revealing natural exposure of one-humped dromedary camels (Camelus dromedarius) to foot-and-mouth disease virus in India - Rout, Manoranjan; Bhatt, Lenin; Mohapatra, Jajati Keshari; Subramaniam, Saravanan; Singh, Rabindra Prasad (Frontiers in Cellular and Infection Microbiology, 2025)
Foot-and-mouth disease (FMD) is one of the most significant animal diseases globally, affecting over 60 susceptible species including camelids particularly Bactrian camels. In order to gather baseline evidence on the current status of FMD in Indian camels, a preliminary random serosurvey was conducted in camels of Rajasthan state with significant camel population. A total of 777 sera collected from one-humped dromedary camels (Camelus dromedarius) across 11 districts of Rajasthan during 2016–2017 were screened for FMD virus (FMDV) 3ABC nonstructural protein (NSP)-antibodies using the commercial PrioCHECK® FMDV NS kit. The sera were further tested using in-house liquid phase blocking (LPB) ELISA to evaluate the level of protective structural protein (SP)-antibody responses against three vaccine strains of FMDV serotypes O, A and Asia 1 if any. Out of 777 serum samples, 117 (15.05%; 95% Confidence Interval: 12.6%-17.7%) tested positive for 3ABC NSP-antibodies indicating the exposure of camels to FMDV. However, none of the sera tested in LPB ELISA showed a protective log10 antibody titre of ≥1.8 against any of the three FMDV serotypes confirming the absence of vaccination in these animals. This report provides retrospective evidence of anti-FMDV antibody response in dromedaries in India. Nevertheless, the role of dromedaries in epidemiology and transmission of FMDV remains unclear, emphasizing the need for further extensive serological screening of a larger number of samples. To the best of our knowledge, the present study, although preliminary, seems to be the first of its kind reporting the evidence of anti-FMDV antibody response in dromedaries in India.